Aspects of Urban Morphology and Socio-Spatial Differences in Urban Space of Alvares Machado City, Sao Paulo, Brazil - Trombeta, Leticia Roberta [UNESP]; Soares, Fernanda Bomfim [UNESP] (Univ Valle, 2015)
This article seeks to contribute to highlight the role of urban morphology in the analysis of production of urban space and differentiation socio-spatial, mainly from the urban forms in the of Alvares Machado City, located in west the of Sao Paulo State. For this there was the relationship between various concepts and theoretical and methodological of production of urban space, socio-spatial differentiation, urban morphology, urban forms and residential allotment, which were needed to understand the urban dynamics established in the city of Alvares Machado, such as : Lefebvre (1972), Sposito (2011) Botelho (2007), Carlos (2007), Capel (2005) Sludge (2011) Whitacker and Miyazaki (2012), Caldeira (2000), Magrini (2013), etc. Thus, it was possible to understand the production of urban space processes that generate socio-spatial differences that territory and its interface with residential allotment as fortified enclaves focused on the real estate consumer market.
Keywords: morphology urban; production of urban space; socio-spatial differences; residential allotment; Alvares Machado City